Brain Neuromodulation Effects on Sport and Nutrition: A Narrative Review - Limone, Pierpaolo; Moscatelli, Fiorenzo; Scarinci, Alessia; Carotenuto, Marco; Messina, Antonietta; Monda, Marcellino; Dipace, Anna; La Marra, Marco; Villano, Ines; Bassi, Paola; Polito, Rita; Messina, Giovanni (Physical Education Theory and Methodology, 2024)
Study purpose. At the end of the twentieth century, the development of highly reliable and painless non-invasive transcranial brain stimulation techniques and devices has aroused great scientific and clinical interest in numerous fields. In neuroscience, since the introduction of innovative and non-invasive devices such as the brain stimulator, the investigation of cortical processes and their neural basis has played a fundamental role. Furthermore, neuroscientists are attracted to therapeutic applications for the treatment of food craving. This narrative review is aimed to explain the growing and constant interest of neuroscientific experimentation in the field of non-invasive transcranial stimulation. Material and methods. After an introduction explaining the historical evolution of NIBS, we will try to provide an overview of the two stimulation techniques (TMS and tDCS); we will describe the different types of stimulation that can be performed using these techniques, the excitatory/inhibitory effects, and the various mechanisms of action at the level of brain activity. Results. We will also provide some elucidations regarding the implications of the facilitative/inhibitory effects, and how these stimulation methods can be used to advance knowledge of the neurofunctional organization of the brain. Conclusion. The results of the study showed the effect of brain neuromodulation on sports and nutrition.